2015
DOI: 10.1515/rjr-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Schneiderian membrane adult vasculogenesis evaluated by CD31 and CD34 expression and morphological arrangement

Abstract: Background. Few studies approached the process of blood vessels formation in the Schneiderian membrane. We aimed at investigating by immunohistochemistry the processes that are responsible for forming new blood vessels in the human Schneiderian membrane. Material and methods. We applied CD31 and CD34 markers on bioptic samples gathered from eight adult patients negative for malignant pathologies. Filopodia-projecting endothelial tip cells (ETCs) were found and indicated processes of sprouting angiogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The vascular regenerative potential of the Schneiderian membrane is dependent on both extrinsic and intrinsic, this condition supported by vasculogenesis and angiogenesis . More recent study showed that evidence of adult vasculogenesis in the maxillary sinus mucosa, with CD31+ and CD34+ cells, these indicated that as highly angiogenic and vasculogenic potentional .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The vascular regenerative potential of the Schneiderian membrane is dependent on both extrinsic and intrinsic, this condition supported by vasculogenesis and angiogenesis . More recent study showed that evidence of adult vasculogenesis in the maxillary sinus mucosa, with CD31+ and CD34+ cells, these indicated that as highly angiogenic and vasculogenic potentional .…”
Section: Discussionmentioning
confidence: 98%
“…Vascularity is an important parameter used in the assessment of healing and regeneration. There are small number of studies, which indicate that angiogenesis is seemingly responsible for remodeling the microvascular bed of the Schneiderian membrane during healing and regenerative processes . In more recent study they studied that Schneiderian membrane adult vasculogenesis evaluated by CD31 and CD34 expression and morphological arrangement and they showed that evidence of vasculogenesis in the maxillary sinus mucosa …”
Section: Introductionmentioning
confidence: 99%